Surjektifitas Pemetaan Eksponensial untuk Grup Lie Heisenberg yang Diperumum - Edi Kurniadi; Putri Giza Maharani; Alit Kartiwa (Jambura Journal of Mathematics, 2023)
The Heisenberg Lie Group is the most frequently used model for studying the representation theory of Lie groups. This Lie group is modular-noncompact and its Lie algebra is nilpotent. The elements of Heisenberg Lie group and algebra  can be expressed in the form of matrices of size 3×3. Another specialty is also inherited by its three-dimensional Lie algebra and is called the Lie Heisenberg algebra. The Heisenberg Lie Group whose Lie Algebra is extended to the dimension 2n+1 is called the generalized Heisenberg Lie group and it is denoted by H whose Lie algebra is h_n. In this study, the surjectiveness of exponential mapping for H was studied with respect to h_n=⟨x ̅,y ̅,z ̅⟩  whose Lie bracket is given by  [X_i,Y_i ]=Z.  The purpose of this research is to prove the characterization of the Lie subgroup with respect to h_n. In this study, the results were obtained that if ⟨x ̅,y ̅ ⟩=:V⊆h_n a subspace and a set  {e^(x_i ) e^(x_j )  ┤| x_i,x_j∈V }=:L⊆H then L=H and consequently Lie(L)≠V.